New Possible Earthquake Precursor and Initial Area for Satellite Monitoring - Vasilev, Atanas; Tsekov, Milen; Petsinski, Petar; Gerilowski, Konstantin; Slabakova, Violeta; Trukhchev, Dimitar; Botev, Emil; Dimitrov, Orlin; Dobrev, Nikolai; Parlichev, Dimitar (Frontiers in Earth Science, 2021)
We propose a new possible earthquake precursor, a coastal water jet originating from shallow water gas seeps and colored by sediments, lifted from increased gas seeps emissions, preceding some earthquakes with offshore epicenters along the Bulgarian Black Sea coast and M ≥ 3. The new possible earthquake precursor is site specific and may be observed in shallow coastal water regions where active faults are accompanied by hydrocarbon gas seeps. We point out to a region where it can be easily detected by direct observation and satellite remote sensing, Zelenka methane seeps (ZMS), near the Bulgarian Black Sea coast. The ZMS activation is related to the tectonic stress and fracturing preceding and accompanying the earthquakes in the Shabla-Kaliakra-Balchik region along the northern part of the Bulgarian Black Sea coast. We also propose an earthquake forecasting experiment, based on the following four hypotheses: 1) The change of the methane emission of shallow horizons is related to crustal strain changes preceding earthquakes in the region; 2) extreme change of the activity of underwater methane seepages appears immediately before nearby earthquakes; 3) shallow water methane seepages activity can be monitored by remote sensing; 4) satellites can register effects from an extreme increase in their emissions. The proposed earthquake forecasting experiment is based on the monitoring of methane seepages activity in the ZMS area by direct observation and remote sensing which may provide indication for preparatory earthquake activity preceding offshore earthquakes in the region.